2014
DOI: 10.7841/ksbbj.2014.29.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Quality Changes of Fresh Vegetable and Fruit Juice by Various Juicers

Abstract: A fresh vegetable and fruit juice has become a new healthy food available for detoxification, dieting and health. This paper presents the useful information about the quality changes of fresh juice according to different juicer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…Owing to the crunchy texture and sweetness of carrots, it can be employed in some fruitlike roles. Choi et al (9) have demonstrated that carrot has the highest α-amylase activity among 12 different vegetables and fruits juice. From the above-mentioned nutritional viewpoint, carrot was chosen as the vegetable for increasing the digestibility, functionality, and palatability of seeds during seed juice preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the crunchy texture and sweetness of carrots, it can be employed in some fruitlike roles. Choi et al (9) have demonstrated that carrot has the highest α-amylase activity among 12 different vegetables and fruits juice. From the above-mentioned nutritional viewpoint, carrot was chosen as the vegetable for increasing the digestibility, functionality, and palatability of seeds during seed juice preparation.…”
Section: Introductionmentioning
confidence: 99%
“…이렇듯 식용 가능한 폴리페놀은 식물에서 천연물까 지 다양하게 분포되어 있으며, 현재까지 8000개 이상의 구조 가 알려져 있다 [1]. 각종 과일은 강력한 항산화 성분들이 풍 부하며 특히 카로티노이드 (carotinoid) 및 플라보노이드와 같은 페놀화합물의 함량이 높다고 알려져 있다 [6]. 과일에 함유된 대표적인 성분으로는 비타민 C, 페놀화합물, 토코페 …”
Section: Introductionunclassified